PEMETAAN DAN ANALISA SUMBER PENCEMAR AIR PERMUKAAN KOTA KETAPANG PROVINSI KALIMANTAN BARAT - Rangga, Boy; Putri Ira, Nurmaya; Ayu Catherine, Liany; Widya Ningrum Palureng, Rurika; Ekamukti Andini, Febby; Rochman, Auliya (Fakultas Teknik Universitas Panca Bhakti, 2024)
Surface water quality is crucial for assessing the sustainability and environmental conditions of aquatic ecosystems. Ketapang City, located downstream of the Pawan River, faces pollution pressure due to various activities, including domestic, industrial, agricultural, livestock, aquaculture, hospitality, healthcare, and other business sectors. This study aims to identify the primary pollution sources affecting the surface water quality of Ketapang City and assess their impact on public health and the environment. The research methods employed include primary and secondary data collection and pollutant source mapping. The findings indicate that the largest pollution source originates from the domestic sector, with a Biochemical Oxygen Demand (BOD) load of 7,200.86 kg/day (7.2 tons/day), Chemical Oxygen Demand (COD) of 6,266.25 kg/day (6.26 tons/day), Total Phosphorus (P) of 249.66 kg/day, Total Nitrogen (N) of 259.41 kg/day, Total Suspended Solids (TSS) of 4,272.64 kg/day (4.27 tons/day), and pesticide contamination of 0.45 kg/day. This study highlights the need for more efficient waste management and improved water pollution policies in Ketapang City. The recommendations include enhancing domestic and industrial waste treatment systems, implementing sustainable agricultural strategies, and conducting regular water quality monitoring to ensure a healthy and sustainable aquatic ecosystem.